Fahr’s syndrome presenting as focal seizures in an adolescent: a case report - Sandhu, Jaskirat Kaur; Kaul, Varun; Sandhu, Kirat Kaur (International Journal of Contemporary Pediatrics, 2024)
Fahr’s syndrome refers to a rare syndrome which is characterized by symmetrical and extensive intra-cranial calcification. It mostly presents in age group 30-40 years or in older adults, although few cases have also been reported in paediatrics. The usual presentation is in the form of movement disorders, cognitive impairment, neuro-psychiatric manifestations etc. Here we report a case of a 14-year-old adolescent male who came to us with complaints of chronic headache and recurrent episodes of focal seizures. His cranial radio-imaging revealed bilateral basal ganglia calcification. On metabolic workup, he was found to have hypocalcemia and secondary hyperparathyroidism, thus confirming the diagnosis of Fahr’s syndrome.